Health Service Use and Mortality of the Elderly Blind - Crewe, J.; Spilsbury, K.; Morlet, Nigel; Morgan, W.; Mukhtar, Syed Aqif; Clark, A.; Semmens, J. (Elsevier Inc., 2015)
Purpose: To determine whether blindness in older people is associated with increased health service use and mortality. Design: Retrospective matched cohort study from July 1, 1999, through June 30, 2010. Participants: A blind cohort 65 years of age and older from a volunteer blind register and a cohort of age- and gender-matched controls selected randomly from the Western Australian electoral roll. Methods: Person-level linked hospital, emergency department (ED), mental health, and death records for the blind and control cohorts were used. Generalized estimating equations assuming a negative binomial distribution were used to estimate relative rates of hospital admissions, lengths of stay, and mortality after adjusting for sociodemographic variables and comorbidity. Emergency department and mental health service visits also were quantified. Main Outcome Measures: Relative rates of hospital admissions, lengths of stay, and mortality, as well as crude proportions of ED and mental health service visits.Results: The blind cohort comprised 1726 individuals alongside 1726 matched controls; 39% were men, and the mean age was 83 years. Combined, the cohorts accumulated a total of 34 130 hospital admissions amounting to 201 867 bed-days. After adjusting for the principal reason for hospital admission and comorbidity, the blind cohort was admitted to the hospital 11% (95% confidence interval [CI], 6%–17%) more often than the control cohort. The blind cohort also stayed in the hospital longer than the controls, but this effect varied by age. Blind participants 65 to 69 years of age spent 88% more days (95% CI, 27%–178%) in the hospital compared with age-matched controls, whereas there was no difference in length of stay between the cohorts by 80 years of age (rate ratio, 1.10; 95% CI, 0.97–1.25). A larger proportion of the blind cohort visited a hospital ED and accessed mental health services compared with the control cohort. Conclusions: Health service use is increased for the elderly blind compared with age-matched controls after accounting for comorbidity. The elderly blind have more hospital admissions, ED visits, and mental health-related visits. The younger elderly blind stay longer in hospital. However, there was no evidence of worse mortality outcomes after adjusting for comorbidity.